Perceptual Information of "An Entirely Different Order": The "Cultural Environment" in The Senses Considered as Perceptual Systems. Issue 2 (3rd April 2017) - Heft, Harry
ABSTRACT: James Gibson's final book, The Ecological Approach to Visual Perception (1979/1986) may have had the unintended effect of overshadowing his prior, seminal work, The Senses Considered as Perceptual Systems (1966). This circumstance is unfortunate because in many ways the final book has a narrower focus. The Senses Considered as Perceptual Systems not only considers other perceptual systems in addition to vision but also it is in this work where Gibson most fully lays out his ecological approach to psychology. In doing so, the book gives more explicit attention to human evolution and sociocultural processes than do his other writings. Although Gibson establishes a framework for considering perception–action commonalities across species, he also examines some of the ways in which perceiving among human and nonhuman animals differ. Among those issues examined are how tool use in the production of pictures and representations has contributed to cultural change, how language can affect perceiving, and how social structures are perceived. The ongoing debate over the conceptual status of affordances is reexamined from the point of view of sociohistorical processes.